Аналіз судової практики у справах про булінг у закладах професійної (професійно-технічної) освіти - Юшкевич, О. Г.; Iushkevych, O. G.; Юшкевич Олена Геннадіївна (Право і безпека. – 2022. – № 1 (84). – С. 81-93, 2022)
Здійснено моніторинг судових рішень, винесених судами у період з 2019 по 2021 рр., щодо булінгу в закладах професійної освіти. Встановлено, що об’єктивну сторону більшості справ становля ть дії здобувачів професійної освіти у формі погроз, побиття ременем, словесних образ, викладання в соціальній мережі принизливих постів, вимагання грошових коштів і невиконання вимог педагогічного працівника. Наголошено, що поширеними адміністративними стягненнями є громадські роботи, попередження, передання правопорушника під нагляд матері та зобов’язання публічно або в іншій формі попросити вибачення в потерпілих; непоодинокими є випадки закриття провадження у справі та взагалі звільнення з огляду на малозначність адміністративного правопорушення від адміністративної відповідальності, обмеж уючись усним зауваженням.

The article is devoted to the monitoring of court decisions rendered by courts in the period from 2019 to 2021. in cases of administrative offenses, the subject of which is the bullying of participants in the educational process at the institutions of professional (vocational) educa-tion. It is determined that the subjects of professional (vocational) education include applicants for professional (vocational) education and teachers who are potential parties to bullying: the offender (buller), the victim (victim of bullying), observers. It is noted that bullying is a consequence of violation by subjects of professional (vocational) education of the rights of other subjects of professional (vocational) education and their re-sponsibilities under general and specialized regulations. It is established that the objective side of most cases is the actions of applicants for professional (vocational) education, which led to psychological and physical violence. It is noted that in bringing juvenile applicants for professional (vocational) education to admin-istrative responsibility on a general basis in most cases, the court imposed an administrative penalty in the form of community service. Emphasis is placed on the fact that the court obliges applicants for professional (vocational) education to pay the court fee, but, given the property status of the minor, the court may re-lease the latter from paying the court fee.
Analysis of judicial practice in cases of bullying at the institutions of professional (vocational) educcation
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; булінг; судова практика; професійна освіта; здобувачі освіти; неповнолітні; bullying; judicial practice; professional education; applicants for education; minors; буллинг; судебная практика; профессиональное образование; соискатели образования; несовершеннолетние